Effect of adding TiO2 nanoparticles on the SEM morphology and mechanical properties of conventional heat-cured acrylic resin - Elnaz Moslehifard; Mahmood Robati Anaraki; Saeed Shirkavand (Tabriz University of Medical Sciences, 2019)
Background. The current study evaluated the compressive, flexural and impact strengths of heat-cured acrylic resins reinforced by TiO2 nanoparticles (NPs). Methods. TiO2 NPs were provided and characterized using scanning electron microscopy (SEM) to determine their morphology and crystalline structure. For three mechanical tests, 12 acrylic resin groups (n=9), totaling 108 specimens, were prepared using a special mold for each test, with TiO2 nanoparticle contents of 0, 0.5, 1 or 2 wt% in different groups. After curing, the compressive, flexural and impact strengths of the specimens were examined according to ISO 1567. Results. In the SEM and XRD study of TiO2 NPs, anatase was identified as the major crystalline phase followed by rutile (average particle size: 20.4 nm). SEM images showed that the nanocomposite with 1 wt% NPs had a more homogenized blend. 1 wt% TiO2 nanocomposite exhibited a higher, but non-significant, impact strength compared to the controls. ANOVA showed significant differences in the impact and flexural strengths between nanocomposites with various contents of TiO2 NPs. Conclusion. The nanocomposite with 1 wt% TiO2 NPs exhibited fewer micro-pores and micro-cracks in the SEM crosssections. A non-significant increase was also observed in the impact strength with TiO2 NPs at 1 wt%. Further increase in TiO2 NPs decreased both the impact and flexural strengths. The compressive strength of the heat-cured acrylic resin was not affected by the incorporation of NPs.